Pengembangan Desain Pembelajaran PAI Berbasis Problem-Based Learning untuk Meningkatkan Kompetensi Spiritual - Rio Pratama; Resky Ananda Putri Erwinsyah; Gusmaneli (CV. ITTC INDONESIA, 2024)
This study examines the development of an Islamic Education (PAI) learning design based on Problem-Based Learning (PBL) to enhance students' spiritual competence. The PBL model is applied to encourage students to identify, analyze, and solve real-life problems related to faith and spirituality. The research methodology involves needs analysis, design development, implementation, and evaluation steps. The findings reveal that the PBL-based learning design can improve students' spiritual competence, including strengthening values such as faith, patience, and noble character. This study recommends PAI teachers adopt the PBL approach to create interactive and relevant learning experiences aligned with students' daily lives.